1998
DOI: 10.1038/sj.bmt.1701524
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of monocyte-dependent T cell inhibitory activity in GM-CSF vs G-CSF mobilized PSC products

Abstract: Summary:This study compares the immune properties of peripheral blood stem cell (PSC) products mobilized with different hematopoietic growth factors (HGFs) as well as apheresis products and peripheral blood leukocytes (PBL) from normal individuals. We found that monocytes in mobilized PSC products appear to inhibit T cell function independent of whether granulocyte colonystimulating factor (G-CSF) or granulocyte-macrophage colony-stimulating factor (GM-CSF) was used for mobilization. In addition, the GF used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…Apoptosis provides one mechanism for the regulation of peripheral CD4 positive T-cell homeostasis. Recent studies suggested that T-cell apoptosis is associated with T-cell activation by either CD3 positive cross-linking, phorbol myristate acetate, or phytohemagglutinin (25,26,(29)(30)(31)(32). This occurs through a MHC nonrestricted monocytedependent mechanism (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptosis provides one mechanism for the regulation of peripheral CD4 positive T-cell homeostasis. Recent studies suggested that T-cell apoptosis is associated with T-cell activation by either CD3 positive cross-linking, phorbol myristate acetate, or phytohemagglutinin (25,26,(29)(30)(31)(32). This occurs through a MHC nonrestricted monocytedependent mechanism (33).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested that T-cell apoptosis is associated with T-cell activation by either CD3 positive cross-linking, phorbol myristate acetate, or phytohemagglutinin (25,26,(29)(30)(31)(32). This occurs through a MHC nonrestricted monocytedependent mechanism (33). The requirement for T-cell activation seems to be a common feature of monocyte-dependent apoptosis mediated by Fas-FasL interaction (30,34,35).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, G-CSF has been shown to increase activation markers on these mobilized cells. 86 Once activated, monocytes in the graft can inhibit T-cell function 87,88 via IL-10 production. 89 Consequently, a shift toward Th2 cytokine production occurs post transplant and may be advantageous for reducing acute GVHD, 90 in which Th1-producing cytokines cause cytotoxic damage to host tissues.…”
Section: Recovery Of Adaptive Immunitymentioning
confidence: 99%
“…6,7 In vitro human studies have demonstrated that PBSC products have high levels of T cell inhibitory activity. [8][9][10][11][12][13] This effect has been variously attributed to the high levels of IL-10 produced by monocytes, 14 to modulation of monocyte function, 15 and more recently, to a mobilisation-associated increase in certain dendritic cell (DC) subsets. 16,17 DC constitute a system of antigen-presenting cells that play a critical role in regulating immune responses.…”
mentioning
confidence: 99%